2019
DOI: 10.1016/j.celrep.2019.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Homeostatic Control of Oligodendroglial Lineage by PDGFRα in Adult Brain

Abstract: Highlights d Oligodendrocyte progenitor cells (OPCs) disappeared and then repopulated in CAGG-iKO mice d Repopulated OPCs are partly derived from pericyte and/or mesenchymal cell population (PC/MC) d PC/MC-derived OPCs differentiate into MBP-expressing mature oligodendrocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 71 publications
0
26
1
1
Order By: Relevance
“…Here, we report the widespread distribution pattern of the C9C5 immunoreactivity in the adult mouse brain and show that C9C5 antibody marks a subset of CC1 + (11-12%), Olig2 + and Sox10 + (3-6%), CAIImature oligodendrocytes as quantified in the cerebral cortex and in the hypothalamus. These cells do not express the PDGFRα signal implicated in OPCs proliferation and in the inhibition of the expression of oligodendroglial maturation markers such as CC1 [18,20]. Thus, these mature oligodendroglial cells constitute a source for delivering Shh to brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report the widespread distribution pattern of the C9C5 immunoreactivity in the adult mouse brain and show that C9C5 antibody marks a subset of CC1 + (11-12%), Olig2 + and Sox10 + (3-6%), CAIImature oligodendrocytes as quantified in the cerebral cortex and in the hypothalamus. These cells do not express the PDGFRα signal implicated in OPCs proliferation and in the inhibition of the expression of oligodendroglial maturation markers such as CC1 [18,20]. Thus, these mature oligodendroglial cells constitute a source for delivering Shh to brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an unbiased analysis of the top 25 differentially expressed genes revealed that SOX10 and PDGFRA are strongly downregulated after cilium induction. Studies have demonstrated that PDGFRA is rapidly downregulated together with oligodendrocyte progenitor (OPC) lineage markers of SOX10 and OLIG2 when OPC differentiate into oligodendrocytes (äặng et al, 2019;Rivers et al, 2008). Notably, downregulation of stemness maintenance and cell cycle regulators implicate cilium induction switches GSCs from self-renewal to differentiation state (Figures S7E and S7F).…”
Section: Cilium Induction Resets the Aberrant Pdgfr-a Signaling In Opc-like Gscsmentioning
confidence: 99%
“…Platelet-derived growth factors (PDGFs) and their cognate receptors compose a signaling network that consists of five ligand-dimers (PDGF-AA, PDGF-BB, PDGF-AB, PDGF-CC, PDGF-DD) and three receptors (PDGFR-αα, PDGFR-ββ, PDGFR-αβ) ( 175 ). While PDGFs have originally been identified as growth factor for smooth muscle cells ( 176 ), they are nowadays viewed as potent inducer of oligodendrocyte proliferation and differentiation ( 177 , 178 ). Interestingly, the PDGF family of cysteine-knot growth factors also includes members of the VEGF subfamily, of which VEGF-B has been shown to induce pro-inflammatory gene expression in astrocytes ( 48 ).…”
Section: Protective Effects Of Reactive Astrocytes Following Cns Insumentioning
confidence: 99%